Efek Konten Dakwah Hanan Attaki di Media Sosial terhadap Tingkat Religiusitas Mahasiswa - Muhamad Farda Setiawan Annafi; Fadhlurrahman Arga Andrian; Ahmad Sunu Aji (Jurnal Humanitaria Jurnal Ilmu Sosial dan Humaniora, 2025)
Social Media is bringing a new direction for da'wah communication in the mass media. Social media, which is dominated by young people, is the most appropriate platform for spreading Islamic da'wah among youth, especially students. Hanan Attaki is one of the lecturers who uses social media as a medium of communication for his da'wah which attracts young people to get to know Islam. This study aims to determine the effect of student audiences on the preaching content of Ustadz Hanan Attaki on social media on their level of religiosity. This study used a qualitative method by conducting interviews with 3 students. The theory used in this study is the theory of new media, the theory of media effects, and da'wah communication. The results of this study are that the preaching content of Hanan Attaki on social media has an effect on the level of religiosity of students, in terms of cognitive, affective, and behavioral effects, all of which show an effect on the level of religiosity that is getting stronger.